Corona virus –A Real Danger Alarm in Pakistan - anwar ali jamali (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2020)
Viral infections are common all over the world. Sometimes they results in out breaks leading to high morbidities and mortalities. Currently in world the infection of corona virus had created a panic situation all over the world targeting the different countries of the world.